The Principle of Entropy Increase: A Novel View of How Tourism Influences Human Health - Hu, Fangli; Wen, Jun; Zheng, Danni; Ying, Tianyu; Hou, Haifeng; Wang, Wei (Journal of travel research, 2025)
The principle of “entropy increase” is a universal law describing a natural progression from order to disorder. This paper is innovatively the first to take the principle as a theoretical basis for assessing how tourism influences human health from a sociomateriality perspective. Despite a growing emphasis on the intersection of tourism and health, there remains a need for further theoretical development in this evolving field—particularly tourism’s positive and negative impacts on physical, mental, and social health based on physiological measures. From an entropy point of view, positive travel experiences could help maintain a low-entropy state (i.e., bodily health) by influencing four key systems. Conversely, negative travel experiences could increase entropy and lead to health issues. An innovative conceptual framework is proposed to illustrate the nexus between tourism and health. This interdisciplinary investigation illustrates a transition in the research paradigm from “health tourism” to “health and tourism.”